Challenging Educational Stereotypes Through the Grass Roots Curriculum Model: Menantang Stereotip Pendidikan Melalui Model Kurikulum Akar Rumput - Mukti, Ebtafil; Tinus, Agus (Universitas Muhammadiyah Sidoarjo, 2025)
In the context of education reform in Indonesia, curriculum innovation at the elementary level remains crucial to address local needs while aligning with national standards. Specifically, Madrasah Ibtidaiyah (MI) Insan Kamil in Tumpang, Malang, has adopted a Grass Roots curriculum development model to integrate Islamic values with contextual learning. However, limited studies have examined the practical application and broader educational impact of this model within Islamic elementary schools, especially its relevance to global educational discourse. This study aims to explore: (1) the design of curriculum development using the Grass Roots approach, (2) managerial strategies in its implementation, and (3) institutional goals in applying the model. The results reveal that the approach empowers educators and communities collaboratively, emphasizing project-based learning that integrates core subjects with local wisdom and Islamic values. The novelty lies in its ability to bridge national curriculum standards with contextualized religious and cultural content, offering a distinct model of grassroots-driven education. This has implications for enhancing student engagement, strengthening local identity, and promoting sustainable, practical learning. The study recommends stakeholder collaboration and improved resource access to optimize this innovative curriculum model in Islamic elementary education. Highlights: Empowers community and educators through collaborative curriculum design. Integrates Islamic values with project-based and contextual learning. Enhances student engagement and promotes sustainable local education. Keywords: Grass Roots Model, Curriculum Development, Madrasah Management, Contextual Learning, Islamic Education